Impacts of Cu and sulfadiazine on soil potential nitrification and diversity of ammonia-oxidizing archaea and bacteria. Issue 1 (1st January 2019) - Liao, Qiang; Li, Mingzhu; Dong, Yuanpeng; Wu, Mi; Meng, Zilin; Zhang, Qian; Liu, Aiju
ABSTRACT: Soil potential nitrification rate (PNR) and diversity of ammonia-oxidizing microbes were investigated in spiked soils with Cu and Sulfadiazine (SDZ). An obvious decrease of PNR was observed with the increase of Cu and SDZ concentrations in the soil. Real-time fluorescence quota PCR result showed that AOA and AOB were slightly stimulated at the gene level in both contaminated soils. Sequential analysis indicated that 200 mg kg −1 Cu could improve AOA diversity but reduce AOB diversity, but 5 mg kg −1 SDZ caused a decrease of both AOA and AOB diversity. Microbial community's analysis also found that 200 mg kg −1 Cu and 5 mg kg −1 SDZ had different influence on the populations of AOA and AOB. It could be concluded that Cu and SDZ might have a different ecological effect mechanism on soil potential nitrification and ammonia-oxidizing microbial communities.